Sustainability-Oriented Innovation for System-Level Impact - Goodman, Jennifer; Halme, Minna; Juntunen, Jouni (Academy of Management, 2025)
The promise of sustainability-oriented innovation (SOI) as a way for firms to positively impact complex, systemic social and environmental challenges is widely embraced but little is known about the system-level impact of SOI. Although previous research suggests that working with stakeholders can enhance such innovation, the escalation of sustainability challenges indicates that we do not yet fully understand how to achieve system-level impact. To address this situation, we develop a framework to operationalize the system-level impact of SOI. We then apply qualitative comparative analysis (QCA) to empirically study different configurations of stakeholder involvement in SOI from 14 firms in eight countries in relation to their system-level impact. We find two distinct recipes for achieving such impact through SOI indicating that firms can choose a radically open collaboration with many non-profit oriented stakeholders or a more targeted approach to collaboration that includes a greater proportion of for-profit partners coupled with a specific impact extender. The equifinality we discover has implications for firm-level decision-making in terms of the type of stakeholders selected and the timing of their involvement. Our results bring systems thinking closer to firm-level action. We additionally identify a role for governmental stakeholders contributing to the renewed interest in management studies around government activities in innovation for complex sustainability challenges.
Keywords: sustainability-oriented innovation; system-level impact; configurational; stakeholders; collaboration; grand challenges; fi=Tuotantotalous|en=Industrial Management|